Analysis of Factors Affecting the Performance of Nursing Nurses Staying in dr. GL Tobing Hospital Tanjung Morawa Medan - Novi Fitriani; Juliandi Harahap; Nuraini Nuraini (Institute of Computer Science (IOCS), 2022)
Nurses are one of the quality improvement factors in hospitals and are the professions that interact the most with patients in explaining and supporting patient problems, explaining nursing diagnoses, explaining interventions to be carried out and providing protection for patient rights. To analyze the factors that influence the performance of inpatient nurses at RSU dr. G.L Tobing in Tanjung Morawa in 2021. The research design used was Cross Sectional with quantitative research with an Explanatory Research approach. The sample of this research is 74 inpatient nurses using total random sampling technique. Analysis of the data used is univariate, bivariate and multivariate analysis with logistic regression test. Based on the results of the logistic test, the value of the cross tabulation between the ability and the performance of nurses with good ability was 27 people and poor ability 47 people and P value = 0.001, the cross tabulation value between compensation and nurse performance, compensation according to 24 people and compensation not appropriate 50 people P = 0.001 while the tabulation value of the work environment with nurse performance, good environment = 47 people and not good 27 people with P = 0.001. There is an effect of ability, work environment and compensation on the performance of inpatient nurses at the General Hospital dr. GL Tobing. It is hoped that the management can maintain the performance of nurses by promoting related trainings and for nurses it is hoped that they will take the initiative in increasing competence by finding sources of information related to the world of nursing.